National Antarctic Data Centre as an essential part of Ukraine researches in Antarctica - L. Globa; V. Lytvynov; I. Moroz (Ukrainian Antarctic Journal, 2012)
The article reviews the main approaches to designing of the National Antarctic Data Centre Internet knowledge-portal. Basic modern technical solutions, underlying software and hardware complex of Internet portal are discussed. In particular, emphasis is made that development of a united information environment Antarctic research data will provide significant economic benefits across the country through the commercialization of their unique data.